School Management to Improve the Quality of Education at the Elementary School Level - Siti Hajar Nurhasanah; Aslamiah Aslamiah; Noorhapizah Noorhapizah; Novitawati Novitawati (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
School management plays a crucial role in improving the quality of education at the primary school level, particularly in optimizing learning processes and educational services. This study aims to examine school management practices in enhancing educational quality at UPTD SD Negeri 3 Batu Tungku, Panyipatan District. The study focuses on three main aspects: school program planning, program implementation, and the challenges encountered during the management process. A qualitative descriptive approach was employed, with data collected through interviews with the principal and teachers, classroom and school-area observations, and document analysis of school plans and evaluations. The findings indicate that school program planning includes curriculum development, teacher competency enhancement, student character development, and improvement of basic school facilities. Program implementation is carried out through coordination between the principal, teachers, and the school committee, yet several challenges persist, such as limited financial resources, fluctuating community participation, and insufficient use of educational technology. The study highlights that improving educational quality requires visionary school leadership, systematic program planning, and strong collaboration among stakeholders. Effective school management has the potential to strengthen learning quality and support continuous improvement in student achievement.